Complex thinking and profile of Colombian university teachers - Vázquez-Parra, José Carlos; Malagón-Castro, Luz Elena; Suarez-Brito, Paloma; Valencia-González, Gloria Clemencia (Frontiers in Education, 2024)
During the last decade, the development of competencies has become a cardinal point for universities, focusing not only on those skills directly associated with technical or disciplinary aspects but also on those necessary in training for life. In this sense, the so-called general (transversal) competencies become primary in the curricula as part of the training of students regardless of discipline. However, although much literature has reported on students' acquisition and development of these competencies, what is the reality for teachers facing this formative challenge? This study utilizes the validated EComplexity instrument to assess self-perceived competency in complex thinking among 51 university teachers (30 women and 21 men, with an average age of 39) from southern Colombia, spanning five academic disciplines: Business, Health Sciences, Engineering, Social Sciences, and Humanities. The objective was to gauge their perceived preparedness to instruct complex thinking as part of a teacher training course, emphasizing the varied academic backgrounds of the involved participants. The study's methodology employed a multivariate descriptive statistical analysis using SPSS software. The results determined that the teachers perceived themselves as competent in complex thinking and sub-competencies. In conclusion, the study found that differences in factors such as gender, age, and academic discipline did not significantly influence teachers' self-perceived competency in complex thinking. This article contributes to the identification of essential teaching skills for the teacher training process within competency-based pedagogical models, ensuring the quality of academic work.